Net Interest Margin, Non-performing Loans, Capital Education Ratio, to Return on Assets of BUMN Banks Listed On The Indonesia Stock Exchange - Hariyanti Hariyanti; Salmiyah Thaha; Lasty Agustuty D (Jurnal Ilmu Manajemen Profitability, 2024)
This study aims to analyze the Net Interest Margin, Non-performing Loans, Capital Education  Ratio, to Return on Assets of BUMN Banks Listed On The Indonesia Stock Exchange. The type of data used in this research is quantitative and qualitative data while the data source used is secondary data. The research was conducted using data from annual published financial reports for a period of 10 years, from 2012 to 2021. The research variables consisted of the independent variables, namely NIM, NPL, CAR, and the dependent variable, namely ROA. The analytical method used is multiple linear regression analysis, and hypothesis testing. Net Interest Margin at BUMN banks has a significant influence on return on assets. Non-performing loans at Bank Mandiri have a significant influence on return on assets, meanwhile at Bank BTN, BRI and BNI, they have no significant effect on return on assets. Capital Education Ratio at BRI bank has a significant effect on return on assets, meanwhile Bank Mandiri, BTN, and BNI have no significant effect on return on assets.